2013
DOI: 10.1155/2013/157810
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electrical Studies of Polyaniline/ZnO Nanocomposite

Abstract: Polyaniline (Pani)/ZnO nanocomposite with diameter 40–50 nm was successfully fabricated by coprecipitation method of ZnO viain situpolymerization of Pani. X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), fourier transformation infrared (FT-IR), UV-Vis absorption spectra, thermogravimetric analysis (TGA), and electrical properties were studied. HRTEM studies showed that the prepared ZnO nanoparticles were uniformly dispersed and highly stabilized throughout the polymer chain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…The peak at about 610 nm has been shifted to lower wavelengths of *558 nm which may be due to the n-p* transitions of quinine-imine groups [28]. These results showed that PAni was completely converted from emeraldine salt to the emeraldine base form by the deprotonation of PAni with NH 4 OH [29].…”
Section: Uv-vis Studiesmentioning
confidence: 86%
“…The peak at about 610 nm has been shifted to lower wavelengths of *558 nm which may be due to the n-p* transitions of quinine-imine groups [28]. These results showed that PAni was completely converted from emeraldine salt to the emeraldine base form by the deprotonation of PAni with NH 4 OH [29].…”
Section: Uv-vis Studiesmentioning
confidence: 86%
“…2.3. In Situ Polymerization.The typical conducting polymers such as PANI and polypyrrole and their composite systems have been extensively studied, thanks to their controllable electric conductivity and other attractive advantages such as bulk processability and dielectric characteristics[45][46][47]. PANI particles or PANI based hybrids with different morphologies have been extensively studied because of their low cost, facile fabrication, and attractive environment stability.…”
mentioning
confidence: 99%
“…Therefore, this is another proof of the formation of the SSARs. On the other hand, T d2 obtained for the SSARs was higher than those obtained to reactive blends of unsaturated polyester resins/St ( T d lower than 390 °C) and a vegetable‐oil‐based hyperbranched polyester‐St copolymer whose T d1 value was 410 °C …”
Section: Resultsmentioning
confidence: 99%